PENGARUH TREATMENT GURINDAM 12 UNTUK MENINGKATKAN INTERAKSI SOSIAL SISWA SMA NEGERI 1 PEKANBARU - Fanny Rahma Pertiwi; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : Purpose of this study was to determine the Effect of Treatment Gurindam 12 to Increase Social Interaction of SMAN 1 Pekanbaru Students. This research is a quantitative research with experimental research type. The population of this study was 35 students, the sample used was 8 students who were indicated to have low social interaction. The technique sampling used in this study was an Experiment with approach one group pre-test and post-test. Data collection techniques used are through questionnaires / questionnaires for students. In this research, the hypothesis proposed is that there are differences in significant students 'social interactions before and after they are given techniques Gurindam 12 and there is a significant influence on techniques Gurindam 12 to increase students' social interactions.In this study, social interaction variables were obtained before being given techniques gurindam 12 included in the low category with a percentage of 25%, moderate category with a percentage of 75%. While after being given technique gurindam 12 social interaction students increased to a high category with a percentage of 62.5%, a medium category with a percentage 37.5%. Social Interaction of 8 students who were previously in the low and moderate category experienced an increase after being given techniques gurindam 12 through group counseling which were mostly in the high category. by 89,4% while 10,6% is influenced by other factors that come from within students and the environment.Key Words: Gurindam 12, social interaction, group counseling